A kingdom of priests : ancestry and merit in ancient Judaism - Himmelfarb, Martha, 1952- (Jewish culture and contexts., 2006)
"According to the account in the Book of Exodus, God addresses the children of Israel as they stand before Mt. Sinai with the words, "You shall be to me a kingdom of priests and a holy nation" (19:6). The sentence, Martha Himmelfarb observes, is paradoxical, for priests are by definition a minority, yet the meaning in context is clear: the entire people is holy. The words also to point to some significant tensions in the biblical understanding of the people of Israel. If the entire people is holy, why does it need priests? If membership in both people and priesthood is a matter not of merit but of birth, how can either the people or its priests hope to be holy? How can one reconcile the distance between the honor due the priest and the actual behavior of some who filled the role? What can the people do to make itself truly a kingdom of priests?"